Effects of Storage Conditions on Gel Characteristics of Soft-Boiled Egg White and Underlying Mechanisms - XIANG Cong, ZHONG Mengzhen, HUO Jiaying, LI Shugang, MA Lulu (Shipin Kexue)
In this study, the effects and underlying mechanisms of storage conditions on the gel properties of soft-boiled egg white prepared from fresh eggs stored at 4 or 25 ℃ for 0–12 days were investigated. The results showed that the texture properties, β-sheet content, and disulfide bond content of egg white gel initially increased and subsequently decreased with storage time, reaching the highest values after 9 days. Disulfide bonds served as the major intermolecular force. Compared with those of fresh samples, the resilience, springiness, β-sheet content, and disulfide bond content of soft-boiled egg white gels from eggs stored for 9 days increased by 16.7%, 29.9%, 16.1% and 22.1% for 4 ℃, and by 34.7%, 32.4%, 30.4% and 25.7% for 25 ℃, respectively, and the microstructure of the samples stored at 25 ℃ for 9 days was more uniform and compact, so it had the best gel properties. Proteomics analysis showed that the abundance of mucin 5B in the 25 ℃/9 days group was 6.4 and 11.4 times higher than that of the 4 ℃/9 days group and the fresh sample, respectively. which may account for its enhanced thermogel properties.